2023
DOI: 10.3390/ma16062138
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nano Hydroxyapatite and Mg-Whitlockite from Biowaste-Derived products via Continuous Flow Hydrothermal Synthesis: A Step towards Circular Economy

Abstract: Biowastes from agriculture, sewage, household wastes, and industries comprise promising resources to produce biomaterials while reducing adverse environmental effects. This study focused on utilising waste-derived materials (i.e., eggshells as a calcium source, struvite as a phosphate source, and CH3COOH as dissolution media) to produce value-added products (i.e., calcium phosphates (CaPs) derived from biomaterials) using a continuous flow hydrothermal synthesis route. The prepared materials were characterised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 108 publications
1
4
0
Order By: Relevance
“…However, it should be noted that DCPA stability is modulated in the presence of Mg 2+ ions [28]. The appearance of the Mg-WH formation under magnesium-rich and mildly acidic and magnesium-rich pH conditions confirms the critical influence exerted by Mg 2+ ions on the stability of DCPA [28]. This influence establishes the requisite conditions for the successful realization of the Mg-WH phase from gypsum via the DCPA phase within the synthesis parameters implemented in our study.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…However, it should be noted that DCPA stability is modulated in the presence of Mg 2+ ions [28]. The appearance of the Mg-WH formation under magnesium-rich and mildly acidic and magnesium-rich pH conditions confirms the critical influence exerted by Mg 2+ ions on the stability of DCPA [28]. This influence establishes the requisite conditions for the successful realization of the Mg-WH phase from gypsum via the DCPA phase within the synthesis parameters implemented in our study.…”
Section: Resultssupporting
confidence: 70%
“…DCPA is known to be the most stable CP phase in solutions with a pH less than 5 [27]. However, it should be noted that DCPA stability is modulated in the presence of Mg 2+ ions [28]. The appearance of the Mg-WH formation under magnesium-rich and mildly acidic and magnesium-rich pH conditions confirms the critical influence exerted by Mg 2+ ions on the stability of DCPA [28].…”
Section: Resultsmentioning
confidence: 84%
“…The sample with the highest magnesium content (5%) exhibits the largest percentage of these platelets and the least number of rods. Whitlockite synthesis was explained by Macha et al [63], and the addition of magnesium to hydroxyapatite was observed to alter particle size in a study presented by Nigar et al, intriguingly, at a higher temperature (i.e., 350 • C) in this system, a tubular morphology of HA and rhombohedral-shaped Mg-WH particles were seen [64].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 68%
“…It was shown earlier that the use of supercritical water in a one-stage continuous hydrothermal process can be implemented for the synthesis of HAp nanorods. , For instance, in ref , HAp nanorods with sizes of 65 × 15 or 140 × 40 nm were produced depending on the selected temperature regime. In the present study, a similar reactor design with the addition of a second mixing stage is used .…”
Section: Introductionmentioning
confidence: 99%